A self-supporting flexible carbon material and its preparation method and application

Through a one-step high-temperature process combined with electrochemical treatment, the activation and element doping of flexible carbon materials are achieved, and the problems of complex and cost of flexible carbon materials preparation processes in the prior art are solved, and self-supported flexible carbon with excellent electrochemical properties are prepared. Material, suitable for high-performance flexible supercapacitors.

CN114512350BActive Publication Date: 2024-12-31ZHEJIANG FORESTRY UNIVERSITY
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202210125570.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-10
Publication Date
2024-12-31
Estimated Expiration
2042-02-10

AI Technical Summary

Technical Problem

The existing flexible carbon materials are made of complex and expensive, making it difficult to achieve low-cost and high-performance industrial production, especially when preparing high-performance flexible supercapacitor electrode materials.

Method used

A one-step high-temperature process is used to combine electrochemical peeling and electrochemical cyclic voltammetry treatment to achieve activation and element doping of carbon materials through electropolymerization and high-temperature heat treatment of nitrogen-containing conductive polymers to prepare a flexible carbon material with self-supporting.

Benefits of technology

It realizes the preparation of flexible carbon materials with excellent electrochemical properties, is suitable for high-performance flexible supercapacitors, is low in cost and simple in process, and is suitable for industrial promotion.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a self-supporting flexible carbon material and its preparation method and application. It comprises the following steps: (1) using carbon felt as a working electrode and a counter electrode respectively, applying electricity in an electrolyte for 2 to 10 minutes, washing and drying, and obtaining an electrochemically stripped carbon felt; (2) using a mixture of nitrogen-containing conductive polymer monomers and alkaline solution as an electrolyte, and using the carbon felt treated in step (1) as a working electrode to construct a three-electrode system for electrochemical treatment, washing and drying, and obtaining a carbon felt loaded with a nitrogen-containing conductive polymer; (3) heat treating the carbon felt obtained in step (2) at 800 to 900°C in a protective gas atmosphere for 1 to 2 hours, cooling to room temperature, and then washing and drying. The present invention can simultaneously complete the two steps of element doping and activation through a one-step high-temperature process, and the prepared flexible carbon material has excellent electrochemical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of flexible electrode material preparation, and specifically relates to a self-supporting flexible carbon material and a preparation method and application thereof. Background Art

[0002] Flexible supercapacitors are a new type of supercapacitor based on flexible substrates, which can be used as energy storage devices for flexible electronic products such as foldable mobile phones, foldable displays, and implantable devices. In recent years, carbon-based materials have become one of the ideal electrode materials for high-performance flexible supercapacitors due to their low toxicity, high conductivity, and excellent electrochemical cycle life. The development of a low-cost, high-performance flexible carbon-based material has become a key step in the commercialization of flexible supercapacitors.

[0003] Compared with traditional powder electrodes, self-supporting flexible electrode materials can be used as both active materials and current collectors. No additional current collectors or binders are required during the preparation process, which effectively solves the problem of easy shedding under high loads. At the same time, they have ultra-high specific capacity and excellent electron transfer ability, and are widely used in the research and development of flexible supercapacitors. For example, graphene carbon nanofiber electrodes, porous carbon nanofiber electrodes, flexible microporous carbon cloth electrodes, multi-level porous carbon nanofiber membrane electrodes, co-doped carbon nanofiber membrane electrodes, nitrogen-sulfur co-doped activated carbon fiber electrodes, etc. can be used in the development of flexible supercapacitors after being prepared through multi-step processes such as in-situ deposition, activation, and post-treatment.

[0004] However, carbon materials such as graphene and carbon nanofibers are difficult to produce industrially due to their complex preparation process and high cost. Therefore, it is highly anticipated that low-cost flexible carbon materials can be used as raw materials to achieve activation and element doping through simple processes to prepare flexible carbon electrode materials that can be used for high-performance flexible supercapacitors. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a self-supporting flexible carbon material and a preparation method and application thereof. After pretreatment, the present invention can simultaneously complete the two steps of element doping and activation through a one-step high-temperature process, and the prepared flexible carbon material has excellent electrochemical properties.

[0006] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:

[0007] A method for preparing a self-supporting flexible carbon material comprises the following steps:

[0008] (1) using carbon felt as a working electrode and a counter electrode respectively, applying electricity in an electrolyte for 2 to 10 minutes, and then washing and drying to obtain electrochemically exfoliated carbon felt;

[0009] (2) using a mixture of nitrogen-containing conductive polymer monomer and alkaline solution as an electrolyte, using the carbon felt treated in step (1) as a working electrode to construct a three-electrode system for electrochemical treatment, washing and drying, and obtaining a carbon felt loaded with nitrogen-containing conductive polymer;

[0010] (3) Heat-treating the carbon felt obtained in step (2) at 800-900° C. for 1-2 h in a protective gas atmosphere, cooling it to room temperature, and then washing and drying it.

[0011] Furthermore, the carbon content of the carbon felt is greater than 99%.

[0012] Furthermore, the electrolyte in step (1) is a sulfate electrolyte.

[0013] Furthermore, the concentration of the sulfate electrolyte is 0.5 to 1 mol / L.

[0014] Furthermore, the sulfate is sodium sulfate, potassium sulfate or ammonium sulfate.

[0015] Furthermore, the positive voltage applied in step (1) is 10 V, and the application time is 4 to 5 minutes.

[0016] Furthermore, in step (2), Ag / AgCl is used as a reference electrode and graphite is used as a counter electrode in the three-electrode system.

[0017] Furthermore, the nitrogen-containing conductive polymer includes, but is not limited to, polyaniline, polynaphthalenediamine or polypyrrole.

[0018] Furthermore, in the electrolyte of step (2), the final concentration of the monomers for forming the nitrogen-containing conductive polymer is 0.2 to 0.5 mol / L; and the final concentration of the alkali solution is 3 to 5 mol / L.

[0019] Furthermore, the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution.

[0020] Furthermore, the processing conditions of step (2) are: scanning speed 20 mV / s, scanning window from 0 to 0.9-1.1 V, and scanning number of circles 13-18 circles.

[0021] Furthermore, the heating rate of the heat treatment in step (3) is 3 to 5°C / min.

[0022] Furthermore, the drying temperature is 80-100° C., and the drying time is 12-24 hours.

[0023] The above preparation method obtains a self-supporting flexible carbon material.

[0024] Application of the above-mentioned flexible carbon material in the preparation of electrode materials.

[0025] The beneficial effects of the present invention are:

[0026] 1. The present invention pre-exfoliates commercial carbon felt electrochemically in a sulfate solution, and expands the carbon layer spacing of the carbon felt through the insertion of anions and the gas generated by the electrochemical reaction; at the same time, oxygen-containing functional groups are introduced on the surface of the carbon felt, which enhances the reaction kinetics and improves the hydrophilicity, thereby facilitating the in-situ growth of polymers on the surface.

[0027] 2. Commercial carbon felt is treated with electrochemical cyclic voltammetry in a mixed solution of monomers such as aniline and alkali, and nitrogen-containing conductive polymers such as polyaniline, polynaphthalene diamine, and polypyrrole are in situ electropolymerized on the surface of the carbon felt. At the same time, the alkali in the solution will be adsorbed on the carbon felt fibers. During the high-temperature heat treatment, the alkali will etch the carbon fibers, thereby generating a large number of micropores and mesopores.

[0028] 3. Nitrogen-containing conductive polymers such as polyaniline are carbonized during high-temperature heat treatment, forming a nitrogen-doped micro-graphitized carbon layer on the surface of the carbon felt fiber, thereby improving conductivity. Therefore, only one high-temperature treatment process is needed to achieve the two purposes of activation and element doping, and the flexible carbon material prepared by the invention has excellent electrochemical properties.

[0029] 4. Using commercial carbon felt as raw material has low cost compared to the preparation of graphene, carbon nanotubes and other materials, which is conducive to industrial promotion. DETAILED DESCRIPTION

[0030] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0031] Example 1

[0032] A self-supporting flexible carbon material, the preparation method of which is as follows:

[0033] (1) At room temperature, two pieces of 1 cm × 4 cm commercial carbon felt were used as the working electrode and the counter electrode, respectively, and a positive voltage of 10 V was applied in 100 mL of 0.5 M sodium sulfate electrolyte for 5 minutes. After that, the commercial carbon felt was taken out and washed with deionized water, and dried in an oven at 80 ° C for 8 h to obtain an electrochemically exfoliated carbon felt;

[0034] (2) Next, at room temperature, 0.2 M aniline monomer and 3 M potassium hydroxide alkaline solution were mixed evenly and 100 mL was taken as the electrolyte. A 1 cm × 4 cm electrochemically exfoliated carbon felt was used as the working electrode, and an Ag / AgCl electrode and a graphite electrode were used as the reference electrode and the counter electrode, respectively. Electrochemical cyclic voltammetry was performed under a three-electrode system: the scan rate was 20 mV s -1 , the scanning window was from 0 to 1 V (relative to Ag / AgCl electrode), the scanning number of circles was 15, after which the material was taken out, washed alternately with deionized water and ethanol for 3 times, and dried in an oven at 80°C for 12 h to obtain a carbon felt-supported polyaniline material;

[0035] (3) The carbon felt-supported polyaniline material was then heated to 800°C for 1 h under a nitrogen atmosphere, then cooled to room temperature, washed with deionized water until neutral, and dried in a vacuum oven at 80°C to obtain a finished self-supporting flexible carbon material.

[0036] Application performance test of the above flexible carbon materials

[0037] This time, its application in supercapacitors was tested. Before the electrochemical properties were tested, the self-supporting flexible carbon material needed to be vacuum degassed in a 1M KOH aqueous solution for 0.5 hours. The self-supporting flexible carbon material was used as the working electrode, the platinum electrode as the counter electrode, and the Hg / HgO electrode as the reference electrode. Using a three-electrode system, the prepared electrode was subjected to constant current charge and discharge tests (charge and discharge voltage range -1 to 0 V) ​​in a 1M KOH electrolyte at room temperature using an electrochemical workstation (CHI 760E, Shanghai Chenhua Instrument Co., Ltd.).

[0038] According to the formula C = I × △t / (S × △V), the specific capacitance C of the prepared sample at different charge and discharge current densities can be calculated based on the charge and discharge curve. Among them, △t (s) represents the discharge time, I (mA) represents the discharge current, △V (V) represents the discharge voltage range, S (cm 2 ) represents the area of ​​active material in the electrode.

[0039] The results show that at 2 mA / cm 2 At this current density, the area specific capacity of the prepared self-supporting flexible carbon material can reach 1468mF / cm 2 , indicating that the self-supporting flexible carbon material prepared by the method of the present invention has excellent electrochemical properties and is a potential candidate for flexible supercapacitor electrode material.

[0040] Example 2

[0041] A self-supporting flexible carbon material, the preparation method of which is as follows:

[0042] (1) At room temperature, two pieces of 1 cm × 4 cm commercial carbon felt were used as the working electrode and the counter electrode, respectively, and a positive voltage of 10 V was applied in 100 mL of 0.8 M sodium sulfate electrolyte for 7 minutes. After that, the commercial carbon felt was taken out and washed with deionized water, and dried in an oven at 80 ° C for 8 h to obtain an electrochemically exfoliated carbon felt;

[0043] (2) Next, at room temperature, 0.5 M aniline monomer and 4 M potassium hydroxide alkaline solution were mixed evenly and 100 mL was taken as the electrolyte. A 1 cm × 4 cm electrochemically exfoliated carbon felt was used as the working electrode, and an Ag / AgCl electrode and a graphite electrode were used as the reference electrode and the counter electrode, respectively. Electrochemical cyclic voltammetry was performed under a three-electrode system: the scan rate was 20 mV s -1 , the scanning window was from 0 to 0.9 V (relative to Ag / AgCl electrode), the scanning number of circles was 13, after which the material was taken out, washed alternately with deionized water and ethanol for 3 times, and dried in an oven at 80°C for 8 h to obtain a carbon felt-supported polyaniline material;

[0044] (3) Then, the carbon felt-supported polyaniline material was heated to 850° C. for 2 h under a nitrogen atmosphere, then cooled to room temperature, washed with deionized water until neutral, and dried in a vacuum oven at 80° C. to obtain a finished self-supporting flexible carbon material;

[0045] The test steps of the application performance of the above-mentioned flexible carbon material are the same as those in Example 1. The results show that at a current density of 1 A / g, the mass specific capacity of the prepared self-supporting flexible carbon material can reach 110.9 F / g, indicating that the self-supporting flexible carbon material prepared by the method of the present invention has excellent electrochemical properties and is a potential candidate for flexible supercapacitor electrode materials.

[0046] Example 3

[0047] A self-supporting flexible carbon material, the preparation method of which is as follows:

[0048] (1) At room temperature, two pieces of 1 cm × 4 cm commercial carbon felt were used as the working electrode and the counter electrode, respectively, and a positive voltage of 10 V was applied in 100 mL of 1 M sodium sulfate electrolyte for 10 minutes. After that, the commercial carbon felt was taken out and washed with deionized water, and dried in an oven at 80 ° C for 8 h to obtain an electrochemically exfoliated carbon felt;

[0049] (2) Next, at room temperature, 0.4 M aniline monomer and 5 M potassium hydroxide alkaline solution were mixed evenly and 100 mL was taken as the electrolyte. A 1 cm × 4 cm electrochemically exfoliated carbon felt was used as the working electrode, and an Ag / AgCl electrode and a graphite electrode were used as the reference electrode and the counter electrode, respectively. Electrochemical cyclic voltammetry was performed under a three-electrode system: the scan rate was 20 mV s -1, the scanning window was from 0 to 1 V (relative to Ag / AgCl electrode), the scanning number of circles was 18, after which the material was taken out, washed alternately with deionized water and ethanol for 3 times, and dried in an oven at 80°C for 10 h to obtain a carbon felt-supported polyaniline material;

[0050] (3) Then, the carbon felt-supported polyaniline material was heated to 900° C. for 1 h under nitrogen atmosphere protection, then cooled to room temperature, washed with deionized water until neutral, and dried in a vacuum oven at 80° C. to obtain a finished self-supporting flexible carbon material;

[0051] The test steps for the application performance of the above-mentioned flexible carbon material are the same as those in Example 1. The results show that at 2 mA / cm 2 At this current density, the area specific capacity of the prepared self-supporting flexible carbon material can reach 1342mF / cm 2 , indicating that the self-supporting flexible carbon material prepared by the method of the present invention has excellent electrochemical properties and is a potential candidate for flexible supercapacitor electrode material.

[0052] Example 4

[0053] A self-supporting flexible carbon material, the preparation method of which is as follows:

[0054] (1) At room temperature, two pieces of 1 cm × 4 cm commercial carbon felt were used as the working electrode and the counter electrode, respectively, and a positive voltage of 10 V was applied in 100 mL of 1 M sodium sulfate electrolyte for 8 minutes. After that, the commercial carbon felt was taken out and washed with deionized water, and dried in an oven at 80 ° C for 8 h to obtain an electrochemically exfoliated carbon felt;

[0055] (2) Next, at room temperature, 0.2 M naphthalene diamine monomer and 4 M potassium hydroxide alkaline solution were mixed evenly and 100 mL was taken as the electrolyte. A 1 cm × 4 cm electrochemically exfoliated carbon felt was used as the working electrode, and an Ag / AgCl electrode and a graphite electrode were used as the reference electrode and the counter electrode, respectively. Electrochemical cyclic voltammetry was performed under a three-electrode system: the scan rate was 20 mVs -1 , the scanning window was from 0 to 1 V (relative to Ag / AgCl electrode), the scanning number of circles was 14, after which the material was taken out, washed alternately with deionized water and ethanol for 3 times, and dried in an oven at 80°C for 10 h to obtain a carbon felt-supported polynaphthalene diamine material;

[0056] (3) Then, the carbon felt-supported polynaphthalene diamine material was heated to 800° C. for 1.5 h under a nitrogen atmosphere, then cooled to room temperature, washed with deionized water until neutral, and dried in a vacuum oven at 80° C. to obtain a finished self-supporting flexible carbon material;

[0057] The test steps for the application performance of the above-mentioned flexible carbon material are the same as those in Example 1. The results show that at 2 mA / cm2 At this current density, the area specific capacity of the prepared self-supporting flexible carbon material can reach 1196mF / cm 2 , indicating that the self-supporting flexible carbon material prepared by the method of the present invention has excellent electrochemical properties and is a potential candidate for flexible supercapacitor electrode material.

[0058] Example 5

[0059] A control example of preparing a self-supporting flexible carbon material by replacing carbon felt with carbon cloth, the preparation method is as follows:

[0060] (1) At room temperature, two pieces of 1 cm × 4 cm carbon cloth were used as the working electrode and the counter electrode, respectively. A positive voltage of 10 V was applied in 100 mL of 0.5 M sodium sulfate electrolyte for 10 minutes. After that, the carbon cloth was taken out and washed with deionized water, and dried in an oven at 80 ° C for 8 h to obtain an electrochemically exfoliated carbon cloth.

[0061] (2) Next, at room temperature, 0.1 M aniline monomer and 4 M potassium hydroxide alkaline solution were mixed evenly and 100 mL was taken as the electrolyte. A 1 cm × 4 cm electrochemically exfoliated carbon cloth was used as the working electrode, and the Ag / AgCl electrode and graphite electrode were used as the reference electrode and the counter electrode, respectively. Electrochemical cyclic voltammetry was performed under a three-electrode system: the scan rate was 20 mV s -1 , the scanning window was from 0 to 1 V (relative to Ag / AgCl electrode), the scanning number of circles was 15, after which the material was taken out, washed alternately with deionized water and ethanol for 3 times, and dried in an oven at 80°C for 10 h to obtain a carbon cloth-supported polyaniline material;

[0062] (3) Then, the carbon cloth-supported polyaniline material is heated to 800° C. for 1 h under a nitrogen atmosphere, then cooled to room temperature, washed with deionized water until neutral, and dried in a vacuum oven at 80° C. to obtain a finished self-supporting flexible carbon material;

[0063] The test steps for the application performance of the above-mentioned flexible carbon material are the same as those in Example 1. The results show that at 2 mA / cm 2 At this current density, the area specific capacity of the prepared self-supporting flexible carbon material is only 123mF / cm 2 , indicating that the self-supporting flexible carbon material prepared by the method of the present invention using carbon cloth instead of carbon felt has certain electrochemical properties, but cannot meet the needs of flexible electronic devices.

[0064] Comparative Example

[0065] The document Chemical Engineering Journal, 2019, 363, 183-191 reports a method for preparing a self-supporting activated carbon felt material, as follows:

[0066] The carbon felt purchased from Anhui Jialiqi Co., Ltd. was carbonized at 900 °C in nitrogen for 4 h, cooled to room temperature, washed with dilute hydrochloric acid solution and deionized water for several times, and dried in an oven at 80 °C for 12 h to obtain a self-supporting activated carbon felt material with a thickness of about 1 mm and an area density of 12 mg / cm 2 The material was prepared as an electrode and its performance was tested in a supercapacitor. The highest mass specific capacity was only 29.5 F / g, which is equivalent to an area specific capacity of 354 mF / cm 2 .

[0067] The performance of the material prepared by this method through a high-temperature activation process cannot meet the energy storage requirements of flexible devices, and the performance of the resulting product is inferior to that of the sample prepared by this method.

Claims

1. A method for preparing a self-supporting flexible carbon material, characterized in that: The following steps are involved: (1) Using carbon felt as the working electrode and counter electrode, respectively, applying electricity in an electrolyte for 2 to 10 minutes, then washing and drying to obtain electrochemically exfoliated carbon felt; (2) using a mixture of nitrogen-containing conductive polymer monomer and alkaline solution as an electrolyte, using the carbon felt treated in step (1) as a working electrode to construct a three-electrode system for electrochemical treatment, washing and drying, and obtaining a carbon felt loaded with a nitrogen-containing conductive polymer; the nitrogen-containing conductive polymer is polyaniline or polynaphthalene diamine; (3) Heat-treating the carbon felt obtained in step (2) at 800-900° C. for 1-2 h in a protective gas atmosphere, cooling it to room temperature, and then washing and drying it.

2. The preparation method according to claim 1, characterized in that: The carbon content of the carbon felt is greater than 99%.

3. The preparation method according to claim 1, characterized in that: The electrolyte in step (1) is a sulfate electrolyte.

4. The preparation method according to claim 1, characterized in that: In the electrolyte of step (2), the final concentration of the nitrogen-containing conductive polymer monomer is 0.2-0.5 mol / L; and the final concentration of the alkali solution is 3-5 mol / L.

5. The preparation method according to claim 1, characterized in that: In the three-electrode system described in step (2), Ag / AgCl is used as a reference electrode and graphite is used as a counter electrode.

6. The preparation method according to claim 1, characterized in that: The electrochemical treatment conditions in step (2) are: scanning speed 20 mV / s, scanning window from 0 to 0.9~1.1 V, and scanning number of 13~18 circles.

7. The preparation method according to claim 1, characterized in that: The heating rate of the heat treatment in step (3) is 3-5°C / min.

8. A self-supporting flexible carbon material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the flexible carbon material according to claim 8 in the preparation of electrode materials.

Citation Information

Cited By

  • Pore-adjustable carbon fiber paper for supercapacitor electrode and preparation method of pore-adjustable carbon fiber paper

    CN121439531A

  • A pore-controllable carbon fiber paper for supercapacitor electrode and a preparation method thereof

    CN121439531B

  • Flexible electrode for supercapacitor and method for its production

    RU2852343C1